JAK2V617F allele burden and thrombosis: a direct comparison in essential thrombocythemia and polycythemia vera - Carobbio, Alessandra (2009)
OBJECTIVE: A direct comparison of the incidence and risk factors of major thrombosis in essential thrombocythemia (ET) and polycythemia vera (PV) according to their respective JAK2V617F allele burden is the object of this study. METHODS: We compared the rate (%/pts/yr) of major thrombosis in 867 ET patients (57% JAK2V617F) with that of 415 PV patients (all JAK2V617F) and examined risk factors. RESULTS: Patients with ET wild type, ET V617F and PV showed a rate of thrombosis of 1.4, 2.1, and 2.7 %/pt/yr respectively. This latter was found to progressively increase according to the time of diagnosis. The actuarial probability of arterial and venous thrombosis in the first 5 years of diagnosis was roughly similar in the three groups. While, in the subsequent periods, the curves of mutated ET patients diverged from wild type and after 10–15 years, ET mutated arm approached PV. CONCLUSION: These findings support the concept of a continuum between ET JAK2 mutated and PV not only in reference to the hematological phenotype but also in terms of vascular events